What's new in clinical obstetric anesthesia in 2015?. (November 2017) - Hess, P.E.
Highlights: Papers from 2015 relevant to the obstetric anesthesia provider are reviewed. Neuraxial anesthesia can be challenging in patients with scoliosis and obesity. Pain after cesarean can be improved with multimodal medications and bundles. Epidural analgesia is associated with fever but is not likely to be causal. No apparent association between epidurals and adverse neurologic outcome. Abstract: Each calendar year the Society for Obstetric Anesthesia and Perinatology invites an individual to conduct a review of the medical literature, identifying clinically relevant publications of interest to the obstetric anesthesia provider. This report of that effort covers the publications from 2015 and includes the categories of anesthesia and analgesia, complications of neuraxial procedures, and the effects of anesthesia on the fetus. Neuraxial procedures represent the foundation of obstetric anesthesia; advances in anesthesia and analgesia include novel modes of administration, and refinements in care of the medically complex patient. In addition to labor analgesia, investigations into post-cesarean recovery address challenges in pain control, patients with obstructive sleep apnea, and treatment protocols intended to improve patient care, notably an enhanced-recovery pathway. Because complications are inevitable, this review identifies investigations on the more common complications of neuraxial procedures, such as hypotension, maternal and fetal bradycardia, and post-dural puncture headache. There were several innovative reports attempting to address these complications, including the use of norepinephrine infusion for the prevention of spinal-induced hypotension, ephedrine for the prevention of fetal bradycardia after combined spinal-epidural analgesia, and pharmacologic treatment of post-dural puncture headache. Not all of these treatments were successful. Finally, there are potential effects of anesthesia on the fetal/neonatal brain, much of which remains poorly defined. An analysis of recent papers suggests that epidural fever is not an independent cause of adverse neurologic fetal injury. On the other hand, evidence continues to grow to support the hypothesis that anesthetic drugs impact neonatal neurologic outcome.